A SYSTEMATIC LITERATURE REVIEW ON METODE ROLE PLAY DALAM MENINGKATKAN KETERAMPILAN BERBICARA ANAK SEKOLAH DASAR - Auliyati, Yetty; Mardiani, Chairina Putri; Wahyudiana, Endang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Speaking skills in elementary school students must be mastered by students for the continuity of communication and social life of students. this study aims to: 1) identify the influence of elementary school students' speaking skills, 2) identify the effectiveness of the role playing method to improve elementary school students' speaking skills the effectiveness of the role playing method to improve elementary school students' speaking skills, 3) analyze publication trends (objectives, methods, and research results) in scientific journals in 2010 - 2022 related to improving speaking skills using the role playing method publication trends (objectives, methods, and research results) in scientific journals in 2010 - 2022 related to improving speaking skills using the role playing method. This journal uses a systematic literature review method with all articles that have been found and processed based on the criteria of inclusion, exclusion, quality assessment then found 11 articles that have been analyzed in accordance with the research questions that have been set. The results of the research are the effectiveness of using the role playing method in improving the speaking skills of elementary school students which has been widely discussed by previous studies including the influence from within students and the influence from outside students, the techniques used in the research in the period 2010 - 2022. Abstrak Keterampilan berbicara pada siswa sekolah dasar harus dikuasai oleh siswa untuk keberlangsungan komunikasi dan kehidupan sosial siswa. penelitian ini bertujuan untuk : 1) mengidentifikasi pengaruh kemampuan berbicara siswa sekolah dasar, 2) mengidentifikasi efektifitas metode role playing untuk meningkatkan keterampilan berbicara siswa sekolah dasar efektifitas metode role playing untuk meningkatkan keterampilan berbicara siswa sekolah dasar, 3) menganalisis kecenderungan publikasi (tujuan, metode, dan hasil penelitian) dalam jurnal ilmiah tahun 2010 – 2022 berkaitan dengan meningkatkan kemampuan berbicara menggunakan metode role playing kecenderungan publikasi (tujuan, metode, dan hasil penelitian) dalam jurnal ilmiah tahun 2010 – 2022 berkaitan dengan meningkatkan kemampuan berbicara menggunakan metode role playing. Jurnal ini menggunakan metode systematic literature review dengan seluruh artikel yang telah ditemukan dan diolah berdasarkan kriteria inklusi,eksklusi,quality assessment kemudian ditemukan 11 artikel yang telah dianalisis sesuai dengan pertanyaan penelitian yang telah ditetapkan. Hasil peneliian berupa efektifitas penggunaan metode role playing dalam meningkatkan keterampilan berbicara siswa sekolah dasar yang sudah banyak dibahas oleh penelitian terdahulu termasuk pengaruh dari dalam diri siswa maupun pengaruh dari luar diri siswa, teknik yang digunakan dalam penelitian dalam kurun tahun 2010 – 2022.